Assessment of Urban Stormwater Quality in Western Australia - Sarukkalige, Priyantha Ranjan; Priddle, S. (IACSIT Press, 2011)
The main aim of this study was to understand the impacts of land use on stormwater quality. Stormwater samples have been collected from three main land use areas; residential, commercial and industrial lands around the Town of Victoria Park in Western Australia. Each sample was tested to measure water quality parameters such as total organic carbon (TOC), suspended solids (SS), total nitrogen (TN), Nitrate Nitrogen (NO3-), Nitrite Nitrogen (NO2−), Ammonia Nitrogen (NH3-N) and total phosphorus (TP). Time variation of stormwater flow, rainfall intensity and stormwater quality clearly showed that the highest concentration of pollutants in stormwater occurs during the first flush event. Further analysis shows that the commercial stormwater demonstrated the cleanest appearing stormwater with lowest amounts of suspended solids whereas the industrial stormwater had the dirtiest appearing stormwater quality. Nutrients in the residential stormwater have the lowest nitrate, ammonia and phosphate concentrations. Overall, the industrial land use site recorded the worst stormwater quality. These results of the preliminary study are only a snapshot of the quality of Western Australia's stormwater runoff, but they emphasize the value of further detailed investigations.